Growth Performance of Heteroclarias Juveniles Fed Graded Levels of Autoclaved Castor Seed (Ricinus communis L.) Cake Based Diets - E. O, Agboola; I. A, Adebayo; B. T, Babalola (International Journal of Aquaculture Research and Development, 2020)
An 84 day feeding trial was conducted on the juveniles (42.51±0.09g) of hybrid catfish, Heteroclarias, in order to evaluate the nutritional potential of 30 minutes autoclaved castor seed cake isonitrogenous (40% crude protein) and isocaloric (3212Kcal/Kg) diets replacing soybean meal at 0, 12.5, 25, 37.5 and 50%, the diets being designated D1, D2, D3, D4 and D5 respectively. Prior to this, the castor seeds (Ricinus communis L.), ZiboCastor No. 3 variety, collected from Ado-Ekiti metropolis, Nigeria were subjected to 0, 20, 30 and 40 minutes autoclaved at 121oC, dehauled, grounded, oil extracted to form cake, then the proximate and antinutrients analysis were carried out. The preliminary tests on the seeds revealed 30 minutes level of autoclaved seeds was the best. The growth performance result showed that there were significant differences (p<0.05) in the mean weight gain (MWG), specific growth rate (SGR), feed conversion ratio (FCR), protein efficiency ratio (PER) and apparent net protein utilization (NPU) among the various diet levels with the progressive decline in the values of each parameter (except FCR that showed progressive increment) along the trend of increment of castor seed cake inclusion (D1, 0%; D2, 12.5%; D3, 25%; D4, 37.5% and D5, 50%). The survival rate followed the same trend of declination with the highest percentage recorded for D1 (93.33±6.67%), followed by D2 (83.33±3.33%), D3 (76.57±3.33%), D4 (66.67±3.33%) and D5 (60.00±5.77%) respectively. Hence the best growth performance and nutrient utilization was shown in D1 (control) followed by D2. It is therefore recommended that autoclaved castor seed cake at 121oC be included at not more than 12.5% inclusion level to reduce cost of feed without necessarily compromising fish growth rate.
Keywords: Castor seed cakes; autoclaving; proximate composition; antinutrients; nutrients utilization; survival rate